Design, implementation, and evaluation of the LOVE teaching package for nursing students - Ramos, Ludivina R.
Summary. The study dealt with the wholeness promoted by listening and communicating, opening to experience, valuing, and empowering (LOVE). Specifically it sought to answer the following questions. 1. What are the effects of the LOVE Teaching Package on nursing students? 2. Is there a significant difference in nursing students along the following dimensions before and after undergoing the LOVE Teaching Package: 2.1. physical 2.2 mental 2.3 emotional 2.4 social 2.5 spiritual. The study had the following objectives : 1. design a teaching module for the course Foundation of Nursing Practice that incorporates the LOVE Teaching Package 2. implement the LOVE Teaching Package 3. evaluate the LOVE Teaching Package in terms of its effects on the physical, mental, emotional, social and spiritual dimensions of nursing students. The participants of the study were one section of third year students enrolled in Foundation of Nursing Practice in the summer term, 2002 at the Saint Louis University College of Nursing in Baguio City. The study used a quasi-experimental one group pretest-posttest design. To compensate for the weaknesses of this design, methodological triangulation was done. Qualitative data were obtained through process documentation and focus group discussions. Other sources of qualitative data were the course worksheets and the 'freedon wall' which consisted of blank sheets of manila paper on which the participants were encouraged to write anything they wanted to write. These data were analyzed using latent content analysis. The themes that emerged from these data as to the effects of the LOVE Teaching Package are the following: 1. Learning of the topic and how to think critically 2. Feeling safe to express one's self and to relate to others 3. Feeling important as a student and as a person 4. Feeling good about one's accomplishments, the learning process itself, and relationships 5. Being responsible for one's learning and for respecting other. Quantitative data were derived from the subjects' answers to a self-report questionnaire, the Rating Scale for the Dimensions of Wholeness. The statistical treatment used was the Wilcoxon signed ranks test. Data analysis showed a significant difference in the physical, mental, emotional, social, and spiritual dimensions of the participants before and after undergoing the LOVE Teaching Package. Conclusions. The following conclusions are drawn from the findings: 1. The LOVE Teaching Package is a growth-promoting experience. 2. The LOVE Teaching Package promotes positive changes on nursing students along the physical, mental, emotional, social, and spiritual dimensions. Recommendations. It is hereby recommended that: 1. Nursing faculty undergo training on the LOVE Teaching Package. They should consider the LOVE Teaching Package as an alternative approach that can effectively promote learning and self-actualization of students. 2. Future researchers conduct other researches on the LOVE Teaching Package or on similar approaches to teaching nursing. These researches should employ a control group to rule out the effects of history, maturation, and testing on the subjects. The use of a control group would validate causation more effectively. It is also recommended that other researches test whether learning of the subject matter is better when the LOVE Teaching Package is used than when it is not used. 3. Program planners for nursing education develop similar programs that promote a holistic approach to teaching.
Dissertation (Doctor of Philosophy in Nursing)--University of the Philippines Manila.
Keywords: Nursing -- Study and teaching -- Philippines; LOVE teaching Package